An Image Tracking Algorithm Based on Object Centre Location and Image NMI Feature - Chen Aibin; Cai Zixing; Dong Deyi (The Sixth International Conference on Fuzzy Systems and Knowledge Discovery : proceedings, Tianjin, China, 14-16 August 2009, 2009)
In order to improve the precision of tracking in real-time, the bandwidth of tracking should be changed according to the change of object's scale. Based on mean shift algorithm and the target center in every frame located by probability method, this thesis puts forward a self-adaptive algorithm for updating views. Then by combining the normalized moment of inertia (NMI) feature, the center of tracking object is located in real-time. The experiments show that this method can choose the proper size of tracking bandwidth when the object size changing and have strong anti-jamming.